PENGARUH FITOREMEDIASI TANAMAN LOKAL TERHADAP KADAR TIMBAL (Pb) TANAH DI LAHAN PENIMBUNAN LIMBAH PERTAMBANGAN EMAS PT. ANTAM - Yessika Evalyana Sinaga Bonor; Kurniawan Sigit Wicaksono; Sri Rahayu Utami (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Gold mining is closely related to land degradation caused by heavy metals such as lead (Pb), which are non-degradable, non-essential, and immobile. This study aims to compare soil lead levels before and after phytoremediation using local plants. Plant species consist of white teak (Gmelina arborea Roxb.) Pulai (Alstonia scholaris L.R.Br.), ganitri (Elaeocarpus ganitrus Roxb.), pine (Pinus merkusii Jungh), rasamala (Altingia excelsa N.) and puspa (Schima wallichii K.) with the planting position on the upper terrace, middle terrace and lower terrace. Soil characteristics observed were texture, spH, and lead content. The two-sample pair test (paired t-test) on the soil before and after phytoremediation had a significant effect on soil lead content (Sig. 1- tailed).